Mental Health Literacy among Health Sciences Students: A Causal-Comparative Study - Gungon, Mharc Justine M.; Gamit, Allysa Denise G.; Lacap, Kimberly S.; Generalo, Robert V.; Vergara, Jerald Q.; Cantilero, Kimberly Ann S. (Future Science / FSH-PH Publications, 2025)
This study examined mental health literacy (MHL), defined as the knowledge and beliefs about mental disorders that facilitate individuals' recognition, management, and prevention of such conditions. This study recruited 326 undergraduate health sciences students from a private university in the City of San Fernando, Pampanga, Philippines. A causal-comparative design was employed, utilizing the Mental Health Literacy Scale (MHLS) to assess students’ knowledge, attitudes, and help-seeking behaviors related to mental well-being. An independent samples t-test revealed no significant difference in MHL scores between female students (M = 123.00, SD = 12.40) and male students (M = 122.00, SD = 13.40), t(324) = 0.812, p = .417, Cohen’s d = 0.09, indicating a negligible effect size. However, a one-way analysis of variance (ANOVA) indicated a statistically significant difference in MHL based on academic programs, F(3, 122) = 5.96, p < .001. Tukey’s post hoc comparisons showed that psychology students (M = 127.00, SD = 12.70) had significantly higher MHL scores than students in nursing (p < .001) and medical laboratory science (p = .004), but not pharmacy (p = .60). These findings suggest that while sex assigned at birth does not significantly influence MHL, academic exposure does. The results highlight the importance of integrating mental health literacy into all health sciences curricula to equip future healthcare professionals with the competencies necessary to support mental well-being in both personal and clinical contexts. This fosters sustainable well-being and strengthens the resilience and responsiveness of the healthcare system.